EXPLORING BIOGENIC AMINES: PHYSIOLOGY, TOXICITY, AND AGMATINE'S CRUCIAL CONTRIBUTION - Fall, Aïcha Diop; Diallo, Amadou Sow; Ndiaye, Mariam Cissé (Global Journal of Chemistry, Biology and Physics (GJCBP), 2023)
Biogenic amines, nitrogen compounds derived from amino acids and protein-rich foods, are present in animals and some plants. At low concentrations, they serve vital physiological roles as neurotransmitters in vertebrates, while high levels can lead to toxicity with varying symptoms depending on the specific biogenic amine. Polyamines like histamine, cadaverine, putrescine, and tyramine can be found in various foods and dairy products, their concentrations influenced by factors such as maturation, storage duration, pH, temperature, and salt content. Monitoring and understanding biogenic amine levels in different contexts, from cancer diagnosis to food safety, is critical. This abstract provides insights into the multifaceted nature of biogenic amines and their importance in both health and food quality.